The effect of a short message service maintenance treatment on body mass index and psychological well-being in overweight and obese children: a randomized controlled trial - De Niet, Judith; Bauer, Stephanie; Kordy, Hans (Pediatric obesity, 2012)
Objective Maintaining weight loss results in childhood obesity treatment is difficult to achieve. Self-management techniques such as self-monitoring are associated with increased weight loss and maintenance. This study analyzes whether self-monitoring of lifestyle behaviours through a short message service maintenance treatment (SMSMT) via mobile phones with personalized feedback positively effects weight, lifestyle behaviours and psychological well-being in obese children. Methods After 3 months of behavioural lifestyle treatment, 141 overweight and obese children (7-12 years) were randomly assigned to an intervention group receiving SMSMT for 9 months (n = 73) or to the control group (n = 68). The intervention group sent weekly self-monitoring data on exercise and eating behaviour and their mood via mobile phones. In return, they received tailored feedback messages. Primary treatment outcomes were weight, eating behaviour and psychological well-being, i.e. competence, self-esteem and quality of life. Secondary outcome was adherence to the SMSMT. Data were analyzed with mixed modelling. Results SMSMT did not improve treatment outcomes. Controls gained temporarily in physical health scores (P = 0.01). SMSMT completers sent on average every 2 weeks an SMS. Children who had greater weight loss during the first 3 months of lifestyle treatment sent more SMSs (P = 0.04). Conclusions We did not find a positive effect of SMSMT on weight, eating behaviour or psychological well-being in obese children. SMSMT seems to be a feasible method of treatment delivery. Future research should study variations of SMSMT to investigate how SMSMT can be more effective.